Information resources for agricultural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
A training seminar on this subject recently brought together about twenty African professionals, documentalists, engineers, agronomists, economists and sociologists in Dakar, Senegal from December 1 5-20, 1986.